Resilience of a microphytobenthos community from the Severn Estuary, UK, to chlorination: A mesocosm approach. (March 2022) - Vannoni, Marta; Créach, Véronique; Ryder, David; Sheahan, Dave
Abstract: The Severn Estuary is a large macrotidal estuary which includes an extensive mudflat with microphytobenthos (MPB) playing a key role in the ecosystem. This study evaluated the impact of chlorination at two different dosing levels (0.05 and 0.5 mg/l as total residual oxidants, TRO, representative of potential concentrations in the mixing zone and within the cooling water systems of a power station) on a MPB community representative of the Severn Estuary. Biomass and diversity were not negatively impacted while physiology was partially affected at the beginning of the experiment, and it recovered towards the end of the experiment. Further investigations for diversity are needed to consolidate our findings. In conclusion our results show that MPB is resilient to chlorination up to a concentration of 0.5 mg/l which is much higher (>10 times) than what might be expected near the chlorinated discharges for most coastal power stations. Highlights: Microphytobenthos communities are resilient to chlorination up to 0.5 mg/l. Biomass and health are not negatively impacted by chlorination after 5 days. Diversity is not affected (statistically) but requires further investigations.